UJI IN VIVO TAHAP PREKLINIS TERHADAP EKSTRAK BATANG PISANG (Musa paradisiaca L.) SEBAGAI ANTIINFLAMASI TOPIKAL - Dewi, Ni Luh Kade Arman Anita; Yuda, Putu Era Sandhi Kusuma; Suarnata, I Gede Agus; Sasadara, Maria Malida Vernandes (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Inflammation is a normal protective response to tissue injury caused by physical trauma, chemical damage, or microbiological substances. Banana stems (Musa paradisiaca L.) have been empirically believed for their topical anti-inflammatory properties. The purpose of this study was to scientifically evaluate the in vivo preclinical anti-inflammatory activity of banana stems. This research was designed experimentally using twenty-five albino male rats which were divided into five groups: the positive control group which received sodium diclofenac gel, the negative control group which received gel basis preparation without any active ingredient, and three experimental groups which received banana stem extract gel in three different concentrations, 5%, 10%, and 15%. Every five rats of every group were firstly injected with 1% of carrageenan, and the anti-inflammatory effect was evaluated every hour for 4 hours using a plethysmometer. The collected data were statistically evaluated. The results showed that banana stem extract gel with concentrations of 15% produced the best anti-inflammatory effect, compared to other gel concentrations. In conclusion, the preparation of 15% banana stem extract gel can be applied as potential topical anti-inflammatory preparation.